If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -1.6 = 5.2 Reorder the terms: -1.6 + 2n = 5.2 Solving -1.6 + 2n = 5.2 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '1.6' to each side of the equation. -1.6 + 1.6 + 2n = 5.2 + 1.6 Combine like terms: -1.6 + 1.6 = 0.0 0.0 + 2n = 5.2 + 1.6 2n = 5.2 + 1.6 Combine like terms: 5.2 + 1.6 = 6.8 2n = 6.8 Divide each side by '2'. n = 3.4 Simplifying n = 3.4
| 6n+4=8n-16 | | x^4=11x^2-18 | | 9=4n-(8n+1) | | 7n-2n+10=3n-16 | | 5y-9=-14+(-14) | | -5y+2=-2(4y+11) | | 6(3+-0.6y)-10y=30 | | 1/5+5=13 | | 18=-6(x+5) | | 2X+1X-59=10 | | d/0.5=11 | | 30000x=45000x-275000 | | -12+29=-4h-17 | | 6(x+9)=15 | | 2y-10+5(-2+0.8y)+4y=180 | | x=4z+y | | 14w-21+5w=51 | | 14+4=X | | 1x-81-21x=-1 | | 31=-9z+24 | | 6x^2+9x+21=0 | | 6x^2-9x-21=0 | | x=8x+14 | | -12y+-40=7y-2 | | 2n^2+8n-42=0 | | 7x-5+3x+15=5x+4y | | -7+8=11 | | 21+(-3)= | | 3x(7x-4)+6x-(13-24x^2)= | | 8x(9)x(2)x(-1)= | | 6x+12=2x-6 | | 14/3b+4/5=15/7b-1/5b-1/3 |